Kajian Karakteristik Agregat Halus Quarry Desa Pulau Terap, Kecamatan Kuok - Aswara, Dana; Setiawan, Beny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The purpose of this study was to conduct an in-depth study of the characteristics of fine aggregates derived from the quarry in Pulau Terap Village, Kuok Sub-District, regarding their suitability for use in the production of normal concrete. The testing of fine aggregates aims to ensure their quality. The following are the tests conducted on fine aggregates: Specific gravity and water absorption test, sieve analysis test, silt content examination, organic content test. These tests are in accordance with SNI 1970-2016 (National Standardization Agency, 2016). Based on the results of the conducted research, conclusions can be drawn that, according to the calculated results from the specific gravity test of fine aggregates, the values obtained are S_d 2.6 and S_s with a value of 2.623. The fineness modulus value is 2.938. The silt content is 2.586%, and the bulk density in compacted state is 1.094468 kg/m3, whereas in loose state, it is 0.949530 kg/m3.